Enhancing Moral and Ethical Judgment through the Use of Case Histories: An Ethics Course for Pre-service Teachers (GIST – Education and Learning Research Journal, 2013)
This article refers to an action research project involving pre-service teachers. The purpose of this study was to determine if specific learning outcomes could be successfully employed as objectives for an ethics course for preservice teacher preparation. Real life case histories were used by students to identify and reflect upon moral and ethical issues. Data was collected through questionnaires, interviews, written reflection, and teacher´s observations. Findings revealed that the set objectives were attainable and apparently achieved by all of the participants. The use of case histories and a color rubric facilitated the development of the students’ moral awareness, reflection and motivation.
Keywords: moral/ethical awareness; reasoning/reflection skills; motivation; conviction; implementation; case histories